2010
DOI: 10.1136/jnnp.2010.205757
|View full text |Cite
|
Sign up to set email alerts
|

Plasma A 42 and A 40 as markers of cognitive change in follow-up: a prospective, longitudinal, population-based cohort study

Abstract: BackgroundSingle measurements of plasma Aβ are not useful in the diagnostics of Alzheimer's disease (AD). However, changes in plasma Aβ levels during repeated testing may be helpful in the prediction and evaluation of progression of the incipient AD or mild cognitive impairment.ObjectiveTo examine the relation of baseline and serial plasma Aβ levels to cognitive change in follow-up.Methods269 subjects (52 cognitively impaired and 217 controls) from a population-based cohort were clinically followed up from 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(65 citation statements)
references
References 52 publications
6
57
2
Order By: Relevance
“…Many candidate markers related to the AD pathophysiology have been tested with promising results, e.g., serum and/or plasma concentrations of the amyloid-beta peptide (Ab 42 ) (Seppälä et al 2010), neurotrophic (Forlenza et al 2010a) and inflammatory factors (Diniz et al 2010), and markers of oxidative stress (Pratico et al 2002). A recent study has concomitantly addressed serum concentrations of several markers of hypoxia, oxidative stress and membrane lipid remodeling with a metabolomics model (Oresic et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Many candidate markers related to the AD pathophysiology have been tested with promising results, e.g., serum and/or plasma concentrations of the amyloid-beta peptide (Ab 42 ) (Seppälä et al 2010), neurotrophic (Forlenza et al 2010a) and inflammatory factors (Diniz et al 2010), and markers of oxidative stress (Pratico et al 2002). A recent study has concomitantly addressed serum concentrations of several markers of hypoxia, oxidative stress and membrane lipid remodeling with a metabolomics model (Oresic et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Our outcome is not a stable trait but rather a moving target with temporal dynamic changes, because previous studies have consistently shown that blood A␤ levels change during the process of AD development. 7,9,12 A single assessment of A␤s may be susceptible to short-term variation. There could also be measurement error of nutrients from the SFFQ, which could bias our results if reporting error is associated with the A␤ measurements.…”
Section: Moderate Alcohol Intake N (%)mentioning
confidence: 99%
“…Although we used caloric intake-adjusted residuals for nutrient variables, we also included caloric intake as a covariate in the models. 25 Finally, in a fully adjusted model, we additionally adjusted for alcohol drinking, use of medication (medications affecting blood vessel thrombus formation propensity including warfarin, heparin, aspirin, and antiplatelet and antidiabetic agents including insulin and oral hypoglycemic), 12,27 and intake of nutrients from supplements (except for MUFA and SFA, for which no supplements were consumed). For nutrients that appeared to be associated with A␤ levels, we further examined their food sources by examining the correlations between foods and the nutrients.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Low plasma Aβ 42 at baseline was associated with cognitive decline occurring during follow up. 43 We found no statistical significance of differences in plasma Aβ 42 levels and Aβ 42 /Aβ 40 ratio among AD, MCI, and HC groups, but there is a tendency that both are lower in aMCI and AD subjects than in HC subjects. Interestingly, plasma Aβ 40 is much higher in AD subjects compared to HC and aMCI subjects.…”
Section: Discussionmentioning
confidence: 47%